2016
DOI: 10.5057/ijae.ijae-d-15-00042
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of UX and Perceptions of Credibility

Abstract: Social Commerce Sites has proliferated on the Mobile Web and Mobile App. However, because virtually anyone can publish this type of information on the Web, consumers cannot always rely on traditional credibility cues such as reputation of a journal. Instead, they must rely on a variety of cues, including visual presentation, to determine the veracity of information. This study demonstrates that users make a judgment of mobile sites' credibility not by contents but by user experiences. Most important factor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The normative approach to decision making argues that importance should only be attributed to the content itself. However, many studies have proved that interfaces can subconsciously influence decision making (Jansson‐Boyd, 2011; Kim, 2016; Robins et al, 2010; Robins & Holmes, 2008). These studies showed that platforms that require touch (such as a touch screen) increased a phenomenon called the endowment effect (Thaler, 1980), an emotional bias that causes individuals to value an owned object higher, often irrationally.…”
Section: Technology and Decision Makingmentioning
confidence: 99%
“…The normative approach to decision making argues that importance should only be attributed to the content itself. However, many studies have proved that interfaces can subconsciously influence decision making (Jansson‐Boyd, 2011; Kim, 2016; Robins et al, 2010; Robins & Holmes, 2008). These studies showed that platforms that require touch (such as a touch screen) increased a phenomenon called the endowment effect (Thaler, 1980), an emotional bias that causes individuals to value an owned object higher, often irrationally.…”
Section: Technology and Decision Makingmentioning
confidence: 99%
“…The first type is ''social link'' commerce; the second type is ''communal purchase'' commerce; the third type is ''online-offline linkage'' commerce (I. J. Hwang, Lee, & Kim, 2014;K. Kim, 2015).…”
Section: Participatory Commercementioning
confidence: 99%